University: An Announcement - Berita Sedimentologi (Ikatan Ahli Geologi Indonesia, 2011)
As Berita Sedimentologi journal aimed to bridge communications, the editor has prepared a special column for the academia, both lecturer and students. In this column, university researchers, lecturers and even students could contribute their articles.Students are welcome to submit their papers related to their laboratory, field studies, or campus academic activities related to sedimentary geology.For students who like to take their opportunity to publish their article, please follow the following guideline:Get permission from supervisorGet permission from the sponsoring company if applicable.Prepare figures such as:MapStratigraphic columnOutcrop photosPrepare the text in EnglishTotal pages including the figures should not longer than 3 pages of A4 size paper. The editors are happy to assist further on the paper preparation.This space will also accommodate news related to student activities such as field trips, seminars, conference, etc. AAPG student chapters, for example, could submit their activity news.